IMPACT OF SEA LEVEL RISE TO COASTAL ECOLOGY: A CASE STUDY ON THE NORTHERN PART OF JAVA ISLAND, INDONESIA - Marfai, Muh Aris (Quaestiones Geographicae, 2014)
The coastline of Indonesia, which borders almost 17,500 islands and the sea and extends for more than 80,000 km, is vulnerable to sea level rise. This paper aims to investigate the impact of sea level rise on coastal ecology in Indonesia focusing on coastal area of Jakarta, Pekalongan, Semarang and Demak in the northern part of Java Island. Geo-spatial data, i.e. satellite images and maps were used to monitor the environmental changes and primary data were obtained through field survey and observation on the specified area. In Jakarta, sea level rise has been predicted to bring great damages to infrastructure in coastal area. Multiple impacts of sea level rise towards mangrove, agriculture, and aquaculture ecosystem occurs in Pekalongan. Semarang coastal area also suffers from the widening spread of health problems as the coastal inundation increases. At the same time, Demak experiences major losses on mangrove and aquaculture ecosystem due to sea level rise.